Wildes Übersetzen Zu Theorie und Geschichte eines literarischen Verfahrens bei Johann Fischart und Arno Schmidt - Trösch, Jodok (Theorie der Prosa, 2023)
This book develops a theory of wild translation. It describes literary strategies that not only serve to translate content but also produce new poetic texts out of foreign linguistic material. Analyses of Johann Fischart's Geschichtklitterung (1575) and Arno Schmidt's Zettel's Traum (1970) examine the function and aesthetic implications of this technique and how it is poetologically negotiated in the texts themselves.